Antibody synthesis within the central nervous system: comparisons of CSF IgG indices and electrophoresis. Issue 3 (March 1983) - Thompson, EJ; Riches, PG; Kohn, J
Abstract : Various laboratories have reported differing success rates in their ability to detect intrathecal synthesis of antibody when comparing the index of [Formula: see text] with electrophoretic analysis. We selected 44 patients in the borderline area of minimal and/or equivocal abnormality by IgG index. Electrophoretic analysis (on polyacrylamide gels for oligoclonal gamma globulin pattern) of parallel specimens was performed at the same time. The number of samples giving a normal index but showing oligoclonal bands varied between 34% and 43% depending on the cut-off point. The views about normal barrier functions underlying such indices are discussed with particular reference to the pathophysiology of the blood-CSF barrier.